Polydactyly a review and update of a common congenital hand difference. Issue 1 (February 2020) - Wessel, Lauren E.; Daluiski, Aaron; Trehan, Samir K.
Abstract : Purpose of review: The purpose of this review is to describe various forms of hand polydactyly and their different treatment approaches. Hand polydactyly is commonly classified as ulnar (small finger) or radial (thumb). Polydactyly can be sporadic, genetic, and/or associated with syndromic conditions. Recent findings: Both ulnar and radial polydactyly can be surgically treated to optimize hand aesthetics and function. Timing of surgery is based on multiple factors, most notably including safety of anesthesia and socialization of the affected child. The pediatrician should be aware of potential associated conditions, such as chondroectodermal dysplasia or Ellis-van Creveld syndrome for ulnar polydactyly. Summary: Polydactyly is a common congenital hand difference and can be broadly be classified by radial or ulnar involvement. Polydactyly warrants hand surgical referral, as surgical treatment is often indicated. Pediatricians should be aware of treatment options, as well as of commonly associated anomalies and syndromes.